The study of school-in-hospital for children with medical needs in Malaysia - Mat So’od , Noor Fatehah; Abdullah, Fadzidah (2012)
The concept of providing special education services to the children with medical needs is relatively a new in Malaysia. During children’s recovering process in any medical centre, their education should not be overlooked as the hospitalized children and young people still need learning activities to maintain a sense of normality in the hospital environment. This study aims to investigate measure of preventing hospitalized children from lagging behind in their studies while undergoing long treatment in hospitals. This issue must be addressed while the children are under treatments, as it influences the children’s academic future. Nevertheless, this study focuses on examining spatial requirements of schools available in hospitals, specifically in Malaysia. The study finds that the educational place for the children should be provided based on their age ranges which are preschool, primary school, and secondary school, to meet the children’s needs of continuous education. Overall, this paper intends to highlight the needs of educational place and spatial requirements for future improvement to the existing schools in hospitals, for the education of children with medical needs, in Malaysia.